Skills Associated With Job Retention Among Persons With Visual Impairments. (September 2022) - Crudden, Adele; McKnight, Zhen Sui
Introduction: The Workforce Innovation and Opportunity Act of 2014 reinforced the state federal vocational rehabilitation program's commitment to job retention and career advancement for persons with disabilities. We continue to have limited information about what job-related skills are most helpful to persons with visual impairments in retaining or advancing in employment.Method: Descriptive statistics and logistic regression were used to investigate the association between current employment status and skills among persons with visual impairments who had a competitive employment history. Data were from a national volunteer survey of persons with visual impairments born between 1950 and 1991. Snowball sampling methods generated the sample.Results: Persons with professional licensure or certificates were more than twice as likely to be employed as those who did not possess these qualifications. Employed participants were less likely to need job-related training to find or keep a job.Discussion: Though additional research to explore the relationships between skills and employment is indicated, persons with visual impairments should be encouraged to explore and pursue job skills training and professional licensure or certification in fields compatible with their career goals.Implications for Practitioners: Even persons with a work history may need additional job skills training to continue employment. Professional licensure or certification may be of value in obtaining employment, but persons with visual impairments may need support to obtain those credentials. Careful career planning to promote positive employment outcomes should include research about the credentials associated with employment goals.